TorakochirurgiaSurgery in the treatment of malignant pleural mesothelioma - Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Malignant pleural mesothelioma (MPM) is a rare aggressive neoplasm, difficult to treat and with negative prognosis. In Poland, the estimated incidence is 400-500 cases a year. The peak of MPM incidence is expected in 2020 in connection with the 30-40-year period of the disease’s development from exposure to asbestos, which was used industrially on a large scale in 1960-1990. Average survival of untreated patients is 4-12 months. MPM treatment results are negative despite implementation of a comprehensive range of treatment methods. Surgery has a central place in the combined treatment of first and second degree MPM. Depending on the disease’s advancement, MPM patients undergo pleurectomy, pleurectomy with lung decortication or extrapleural pneumonectomy. So far, no prospective, randomised research into treatment results of MPM patients subjected to pleurectomy as compared with patients treated with extrapleural pneumonectomy has been conducted. The evaluation of MPM treatment is rather difficult as a result of there being only a small number of presented groups as well as varied schemata of the implemented treatment.